Pengaruh inflasi terhadap pengangguran Kalimantan Barat - B01110047, Marselina Elin (Jurnal Pembangunan dan Pemerataan, 2014)
This studyentitled"The Effect ofInflationand Economic GrowthAgainst Unemployment inWest Kalimantan", whichaimsto testandanalyze"The Effect ofInflationandEconomic GrowthAgainstUnemployment inWest Kalimantan in 1993-2012". The method usedto testandanalyzethese relationshipsisa methodof datatime series, using secondary dataobtainedfrom thetime seriesof publicationsCentral Statistics Agency (BPS), the Department ofManpower andTransmigrationandBAPPEDAWest Kalimantan. Analisis of the data in this study using multiple linear Regression Method, Classical Assumption Test, test hypotheses using parsial testing (t test) simultaneous ( f test) and Test the Coefficient of Determination.the data used in this study is data Inflation, Economic Growth and the Unemployment Rate in West Kalimantan in 1993-2012. The results ofthe calculationandanalysisof data, itcan be explainedthat thepositive effectof inflationon the unemployment ratebutnotsignificantlyobtained t value of(0.186416>0.1), thushypothesis1is rejected. significanteconomicgrowth intheunemployment ratet value of(-1.897376 <0.1).This impliesthateconomicgrowthhas anegative and significant impacton the unemployment rate, so the hypothesistwois accepted. The test resultssimultaneouslyobtained F value of1.856706to0.186499significance of>0.1. Retrievedcalculated F value(1.856706)<F table(2.11).Thismeans thatthe unemployment rateis notaffected byinflationandeconomicgrowthtogether. Keywords: Inflation, Economic Growthand Unemployment.